Land tenure and management of trees: the case of customary land areas of Ghana - Otsuka, Keijiro; Quisumbing, Agnes R.; Payongayong, Ellen; Aidoo, J. B. (International Food Policy Research Institute, 1998)
Customary land areas in Western Ghana have been evolving towards individualized ownership. Inherited and temporarily allocated family lands are being transferred to wives and children as inter-vivos gifts, to be planted with cocoa. Giving gifts is a way to circumvent the traditional Akan matrilineal land inheritance system in which land is transferred from a deceased man to his matrilineal relatives but not to his wife and children. This study examines the effects of this process of individualization on the production efficiency of cocoa and food crops using detailed household-level data from 249 households in 10 villages in Western Ghana.....Given that a major proportion of labor input into young cocoa cultivation is provided by women and children, it is not surprising that gift transactions have evolved to increase their incentive to provide labor in establishing cocoa. There are also no significant gender differences in either net revenue per hectare or labor use per hectare. Thus, the transfer of land to women through gifts has improved gender equity without sacrificing production efficiency.